The Responsibility of Military Command in the Enforcement of Humanitarian Law: A Case Study of the Russia–Ukraine Conflict - Nadi Chaidir; Dedi Iryanto; Tarsisius Susilo; Rahman Yadi; Joko Prasetyo (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
International humanitarian law (IHL) imposes a strict obligation on military leaders to protect civilians and prevent their troops from committing violations through the principle of command responsibility. However, field practices often deviate, especially during the Russia-Ukraine conflict that escalated since February 2022. This research aims to (1) describe the normative framework of command responsibility, (2) analyze the implementation of command accountability in the conflict, and (3) provide strategic recommendations to enhance the enforcement of IHL. The research design uses a normative-qualitative approach with case studies, where international legal instruments (Geneva Conventions, Additional Protocol I, Rome Statute) and International Criminal Court rulings are used as primary sources. Secondary data in the form of reports from leading NGOs (Human Rights Watch, Amnesty International, ICRC) and peer-reviewed academic literature were analyzed through content analysis to examine the elements of knowledge, prevention, and enforcement by military commanders. Source triangulation and peer debriefing ensure the validity and reliability of the findings. The research findings reveal patterns of serious violations, including indiscriminate attacks, forced displacement of civilians, and destruction of humanitarian facilities, occurring without adequate prevention or enforcement efforts by the military command. Political obstacles, destruction of evidence, denial of jurisdiction, and limited institutional capacity hinder accountability. In conclusion, although the HHI framework has matured, its implementation requires strengthening scenario-based training, revising standard operating procedures for rapid investigations, and access protocols for international investigators. Further studies are recommended to involve field interviews and internal document analysis to enrich the understanding of command responsibility practices. Keywords: Command accountability, Command responsibility, Enforcement of law, International humanitarian law, Russia–Ukraine conflict